Clinical characteristics and outcomes of critically ill coronavirus disease 2019 patients in Malaysia during the first wave: A multi-center observational study (COVIDICU-MY) - Ab Rahman, Noor Iftitah; Yunos, Nor’azim Mohd; Atan, Rafidah; Mariapun, Jeevitha; Ab Rahman, Mohd Ali‘Imran; Ismail, Abdul Jabbar; Deva, Shanti Rudra (Frontiers in Medicine, 2023)
Background: COVID-19 emerged with a wide range of clinical presentations; Malaysia was not spared from its impact. This cohort study aimed to record the clinical characteristics of COVID-19 patients admitted to ICU, their clinical course, treatments, and hospital outcomes. Results: 170 critically ill patients were included, with 77% above 50 years of age (median age 60, IQR (51-66)) and 75.3% male. Hypertension, diabetes mellitus, hyperlipidemia, chronic cardiac disease, and chronic kidney disease were most common among patients. A high SAPS II score (median 45, IQR (34-49)) and SOFA score (median 8, IQR (6-11)) were associated with mortality. Patients were profoundly hypoxic with a median lowest PF ratio of 150 (IQR 99 - 220) at admission. 91 patients (53.5%) required intubation on their first day of admission, out of which 38 died (73.1% of the hospital non-survivors). Our cohort had more patients with moderate Acute Respiratory Distress Syndrome, 58 patients (43.9%), compared to severe ARDS, 33 patients (25%); with both ARDS classification groups contributing to 25 patients (54.4%) and 11 patients (23.9%) of the non-survival group respectively. Cumulative fluid balance over 24 hours was higher in the non-survival group with significant differences on Day 3 (1953 versus 622 ml, p < 0.001) and Day 7 of ICU (3485 vs 830 ml, p < 0.001). Patients with high serum creatinine, urea, lactate dehydrogenase, aspartate aminotransferase and d-dimer, and low lymphocyte count throughout the stay also had a higher risk of mortality. The hospital mortality rate was 30.6% in our cohort. Conclusion: We report high mortality amongst critically ill patients in multi-ICU centres in Malaysia, at 30.6%, during the March to May 2020 period. High admission SAPS II and SOFA, and severe hypoxemia and high cumulative fluid balance were associated with mortality. Higher creatinine, urea, LDH, AST and d-dimer, and lymphopenia were observed in the non-survival group.